2013
DOI: 10.1287/opre.2013.1213
|View full text |Cite
|
Sign up to set email alerts
|

The Wisdom of Competitive Crowds

Abstract: When several individuals are asked to forecast an uncertain quantity, they often face implicit or explicit incentives to be the most accurate. Despite the desire to elicit honest forecasts, such competition induces forecasters to report strategically and nontruthfully. The question we address is whether the competitive crowd's forecast (the average of strategic forecasts) is more accurate than the truthful crowd's forecast (the average of truthful forecasts from the same forecasters). We analyze a forecasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Lichtendahl Jr. et al ( 2013) establish a limiting equilibrium in a normal model where winner-take-all contests elicit self-extremized expert predictions in large crowds of experts. Note that for K = N and N → ∞, the optimal weight on private signals is one for any l > 0 and we have α 2 → 1 in the equilibrium above . Lichtendahl Jr. et al (2013) also show that, depending on the parameters, the limiting weight on the private signal is one either in a symmetric pure strategy equilibrium or in a mixed strategy equilibrium where experts provide a noisy report of their private signal only.…”
Section: Pekersupporting
confidence: 59%
See 3 more Smart Citations
“…Lichtendahl Jr. et al ( 2013) establish a limiting equilibrium in a normal model where winner-take-all contests elicit self-extremized expert predictions in large crowds of experts. Note that for K = N and N → ∞, the optimal weight on private signals is one for any l > 0 and we have α 2 → 1 in the equilibrium above . Lichtendahl Jr. et al (2013) also show that, depending on the parameters, the limiting weight on the private signal is one either in a symmetric pure strategy equilibrium or in a mixed strategy equilibrium where experts provide a noisy report of their private signal only.…”
Section: Pekersupporting
confidence: 59%
“…Study 2 also implemented a winner-take-all contest as an alternative incentive-based solution to elicit self-extremized expert judgments. Lichtendahl Jr. et al (2013) derived the limiting equilibria in a winner-take-all contest where experts self-extremize. The resulting average forecast is more accurate than the average of nonextremized forecasts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ottaviani & Sørensen [28] and Lichtendahl & Winkler [29] have shown that forecasters who compete to be the most accurate have an incentive to not report their true opinion. Lichtendahl et al [30] have shown that an advice seeker benefits from setting up an incentive scheme that rewards strategic behaviour. The rationale is that the variance of the quantity predicted by the experts is greater under a competitive scheme.…”
Section: Incentive Systemsmentioning
confidence: 99%